A Systematic Review to Explore the Scope of Global Interventions to Reduce the Incidence of Gastric Cancer - Shrivastava, Saurabh Ram Bihari Lal; Shrivastava, Prateek Saurabh; Ramasamy, Jegadeesh (Cancers Review, 2014)
Globally, gastric cancer has been acknowledged as a disease of public health concern because of its related morbidity, deaths and influence on multiple dimensions of the quality of life of the patient and their family members. The objective of this article is to systematically review the published literature on the potential risk factors of gastric cancer, and eventually suggest range of interventions to eventually minimize the prevalence of gastric cancer. An extensive search of all materials related to the topic was made using library sources including Pubmed, Medline, World Health Organization website and Google scholar searches for one month. Keywords used in the search include Gastric cancer, health, and Helicobacter pylori. Multiple ranges of factors have been attributed to the causation of gastric cancer in heterogeneous settings. To counter the consequences of gastric cancer, there is a crucial need to develop and implement a public health strategy to enable early detection of the cancer. In conclusion, in the global aim to reduce the burden of gastric cancer, the need of the hour is to formulate comprehensive & cost-effective strategies well supported by intensified awareness campaigns and strengthening of the health care delivery system.